Preventing Stunting from the Source: A Study of Premarital Couples on Participation in Preconception Care - Nuriana Kartika Sari; Ismiyati, Atik; Hernayanti, Munica Rita; Sumarah, Sumarah; Siscadarsih, Indraswari (Poltekkes Kemenkes Yogyakarta, 2025)
Indonesia ranks among the highest globally for childhood stunting, largely due to chronic nutritional deficiencies beginning during the first 8000 days of life—starting even before conception. Poor health and nutritional status among women of reproductive age prior to marriage significantly increase the risk of adverse pregnancy outcomes and childhood stunting. This study aimed to identify the determinants of premarital couples’ participation in preconception care as a strategy to reduce stunting. This cross-sectional analytical study involved 61 premarital couples recruited through total sampling at the Office of Religious Affairs (KUA) in Kapanewon Sewon, Bantul Regency, Yogyakarta, Indonesia. Inclusion criteria included couples aged 20–35 years who met the study requirements. Data were analyzed using univariate, bivariate (Chi-square), and multivariate logistic regression tests. Knowledge (p = 0.001), attitude (p = 0.007), and social support (p = 0.015) were significantly associated with participation in preconception care. Multivariate analysis showed that couples with good knowledge were 4.3 times more likely (AOR = 4.30; 95% CI: 1.65–11.22) to participate in preconception care. Improved knowledge, positive attitudes, and strong social support significantly increase premarital couples’ participation in preconception care. Strengthening early health promotion and community-based interventions is essential to optimize reproductive health preparation and prevent stunting from its earliest source.